2023
DOI: 10.1590/1806-9282.20230022
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels in patients with seborrheic dermatitis

Abstract: SUMMARY OBJECTIVE: Seborrheic dermatitis is a common papulosquamous skin disease with unknown pathogenesis. The aim of our study was to determine the serum level of 25-hydroxy vitamin D in patients with seborrheic dermatitis SD. METHODS: A total of 53 patients and 60 healthy controls were included in the study. Serum vitamin D, calcium, phosphorus, and parathormone levels were measured in the patient and control groups, and a comparison was made between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…This is supported by a case-control trial comparing the level of 25-hydroxyvitamin D in patients diagnosed with SD to healthy controls, and they've established that serum vitamin D was significantly lower in the SD group (p=0.007) and a low level was also associated with an increased severity of scalp SD (P= 0.003) [19]. Another study investigated the effects of Vitamin D supplementation on recurrences of SD in 32 patients and found that 65% of them had a reduction in the number of disease recurrences during treatment, yet 12.5% suffered an increase in the frequency of disease attacks [20].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by a case-control trial comparing the level of 25-hydroxyvitamin D in patients diagnosed with SD to healthy controls, and they've established that serum vitamin D was significantly lower in the SD group (p=0.007) and a low level was also associated with an increased severity of scalp SD (P= 0.003) [19]. Another study investigated the effects of Vitamin D supplementation on recurrences of SD in 32 patients and found that 65% of them had a reduction in the number of disease recurrences during treatment, yet 12.5% suffered an increase in the frequency of disease attacks [20].…”
Section: Discussionmentioning
confidence: 99%